2021
DOI: 10.3389/fimmu.2021.678918
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Role and Therapeutic Potential of Non-Coding RNAs Mediated by Dendritic Cells in Autoimmune and Immune Tolerance-Related Diseases

Abstract: Dendritic cells (DCs) are professional antigen-presenting cells that act as a bridge between innate immunity and adaptive immunity. After activation, DCs differentiate into subtypes with different functions, at which point they upregulate co-stimulatory molecules and produce various cytokines and chemokines. Activated DCs also process antigens for presentation to T cells and regulate the differentiation and function of T cells to modulate the immune state of the body. Non-coding RNAs, RNA transcripts that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Finally, it is worth noting that lncRNAs might participate in the immunopathogenesis of CanL, as they are critical regulators of gene transcription during immune response through regulating protein-protein interactions or via their ability to assemble with RNA and DNA (147)(148)(149)(150). Accordingly, we found that changes in the expression of several lncRNAs were significantly associated with CanL, including an antimicrobial peptide NK-lysin-like (LOC608395) and JUN, which play immunomodulatory roles (151,152).…”
Section: Regulation Of Gene Transcription: Lncrnas and Chromatin Organizationmentioning
confidence: 76%
“…Finally, it is worth noting that lncRNAs might participate in the immunopathogenesis of CanL, as they are critical regulators of gene transcription during immune response through regulating protein-protein interactions or via their ability to assemble with RNA and DNA (147)(148)(149)(150). Accordingly, we found that changes in the expression of several lncRNAs were significantly associated with CanL, including an antimicrobial peptide NK-lysin-like (LOC608395) and JUN, which play immunomodulatory roles (151,152).…”
Section: Regulation Of Gene Transcription: Lncrnas and Chromatin Organizationmentioning
confidence: 76%
“…The ability to produce cytokines is well known as the symbol of DC function (18,19). Previous studies have shown that hemorrhagic shock induced the dysfunction of cytokine production, such as TNF-α, IL-6, IL-10, IL-12, and so on, in splenic DCs (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…DC-mediated non-coding RNA also plays a vital role in autoimmune diseases. 53 In addition to directly affecting autoimmune diseases, DCs exhibit immunosuppressive activity. Immune tolerance can be maintained by regulating DC function.…”
Section: Dendritic Cells and Autoimmune Diseasesmentioning
confidence: 99%
“…The number of DCs in the peripheral blood of patients with autoimmune diseases increases. DC‐mediated non‐coding RNA also plays a vital role in autoimmune diseases 53 …”
Section: Dendritic Cells and Autoimmune Diseasesmentioning
confidence: 99%